KOMUNIKASI KEBIJAKAN PUBLIK DALAM PENGEMBANGAN DESA WISATA DI KAMPUNG ADAT CIREUNDEU - Emi Rachmawati; Rannie Dyah K Rachaju; Dina Alamianti (Dialektika, 2019)
The objects of tourism attraction have an important role in Indonesia’s tourism growth, as an example is Cireundeu adat village in Cimahi, West Java. Which has potentials to be a tourism destination, and still being developed of late. The potentials to be a tourism destination cannot be separated from local government involvement to the development of village tourism, which can be done through regulation and authorization, but in the enactment process, there are several factors that make policy implementation of Cirendeu adat village development as tourism destination is not optimal. The purpose of this research is to know the implementation on communication of public policy, particularly about the development of tourism village in Cireundeu Adat Village that led by the Department of Culture, Tourism, Youth and Sports (Disbudparpora) as an Executive element. This research uses qualitative research methods with data collection procedures are through observation, in-depth interviews, and related documentation. This research concludes that the communication on public policy of village tourism development led by Disbudparpora was through persuasive communication approach, along with that, there are constrain factors and supporting factors in the implementation. Disbudparpora also must actively provide guidance in development process and more engaging with the indigenous peoples for sustainable tourism development.